Table of Contents and Forewords of the TAWARIKH Journal, issue of April 2015 - TAWARIKH, Editor Journal (ASPENSI in Bandung, Indonesia, 2015)
This journal, with ISSN 2085-0980, was firstly published on October 28, 2009. Since issue of April 2012 to April 2014, the TAWARIKH journal was organized by the Lecturers of History Education Department FKIP UVRI (Faculty of Education and Teacher Training, Veteran University of the Republic of Indonesia) in Makassar. Since issue of October 2014 to date, the TAWARIKH journal has jointly been organized by the Lecturers of History Department FIB UNHAS (Faculty of Humanities, Hasanuddin University) and LP2M (Research Institute and Community Service) UNHAS in Makassar, South Sulawesi, Indonesia; and published by Minda Masagi Press as a publishing house owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. This journal is published twice a year i.e. every October and April. For period of 2012 to 2017, the TAWARIKH journal has been accredited by Ditjendikti Kemdikbud RI (Directorate-General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia).Makassar, Indonesia: April 28, 2015.Prof. Dr. Dwia Aries Tina PulubuhuHonorable Patron of the TAWARIKH Journal in Bandung, West Java; and Rector of UNHAS (Hasanuddin University) in Makassar, South Sulawesi, Indonesia.